Lexicology of the Toponymical Name of Bekasi City, West Java Province - Ahmad Khoiril Anam; Zainal Rafli; Samsi Setiadi (Hortatori : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
The purpose of this study is to analyze in depth and critically about Lexicology in the Toponymy of Bekasi City. The method used in this study is ethnolinguistics which uses a descriptive qualitative approach.  The object of this study includes the results of the observation in the form of recordings of interviews and literature in the form of a manuscript of the Bekasi History Book (Since the Buni Ampe Wayah Gini Civilization), by Endra Kusnawan at the Bekasi Toponymy Subbab. Based on data analysis, the author can conclude that the name changes from the name Candrabhaga to finally change to the   name Bekasi through a lexicological process which includes: the composition process, the process of metathesis, the process of adaptation, the process of ellipsis, the process of assimilation, and the process of apocope.Keywords: Lexicology; toponymy; name; Bekasi.